Immunosuppressive Effects of the Traditional Chinese Herb Qu Mai on Human Alloreactive T Cells. Issue 5 (22nd February 2013) - Reid‐Adam, J.; Yang, N.; Song, Y.; Cravedi, P.; Li, X‐M.; Heeger, P.
<x xml:space="preserve">Abstract</x> Current therapies for transplant rejection are suboptimally effective. In an effort to discover novel immunosuppressants we used cytokine ELISPOT and ELISAs to screen extracts from 53 traditional Chinese herbs for their ability to suppress human alloreactive T cells. We identified a dichloromethane‐soluble fraction (Qu Mai fraction AD [QMAD]) of Qu Mai (Dianthus superbus) as a candidate. High‐performance liquid chromatography (HPLC) analysis of QMAD revealed three dominant peaks, each with a MW ∼600 Daltons and distinct from cyclosporine and rapamycin. When we added QMAD to human mixed lymphocyte cultures, we observed dose‐dependent inhibition of proliferation and IFNγ production, by naïve and memory alloreactive T cells, and observed an increased frequency of Foxp3+CD4+ T cells. To address whether QMAD induces regulatory T cells we added QMAD to anti‐CD3/CD28‐stimulated naïve CD4 T cells and observed a dose‐dependent upregulation of Foxp3 associated with new suppressive capacity. Mechanistically, QMAD did not induce T cell IL‐10 or TGFβ but blocked T cell AKT phosphorylation, a key signaling nexus required for T cell proliferation and expansion, that simultaneously prevents Foxp3 transcription. Our findings provide novel insight into the antiinflammatory effects of one traditional Chinese herb, and support the need for continued isolation, characterization and testing of QMAD‐derived components as immune suppressants for transplant rejection.